Fermentation of Nocellara Etnea Table Olives by Functional Starter Cultures at Different Low Salt Concentrations - Pino, Alessandra; De Angelis, Maria; Todaro, Aldo; Van Hoorde, Koenraad; Randazzo, Cinzia L.; Caggia, Cinzia (Frontiers in Microbiology, 2018)
Nocellara Etnea is one of the main Sicilian cultivar traditionally used to produce both olive oil and naturally fermented table olives. In the present study, the effect of different salt concentrations on physico-chemical, microbiological, sensorial and volatile organic compounds (VOCs) formation was evaluated in order to obtain functional Nocellara Etnea table olives. The experimental design consisted of 8 treatments as follow: fermentations at 4%, 5%, 6% and 8% of salt with (E1-E4 samples) and without (C1-C4 samples) the addition of starters. All the trials were carried out at room temperature (18 ± 2 °C) and monitored for an overall period of 120 d. In addition, the persistence of the potential probiotic Lactobacillus paracasei N24 at the end of the process was investigated. Microbiological data, revealed the dominance of lactic acid bacteria (LAB), starting from the 7th d of fermentation, and the reduction of yeasts and enterobacteria in the final product inoculated with starters. VOCs profile highlighted a high amount of aldehydes at the beginning of fermentation, which significantly decreased through the process and a concomitant increase of alcohols, acids, esters and phenols. In particular, esters showed an occurrence percentage higher in experimental samples rather than in control ones, contributing to more pleasant flavours. Moreover, acetic acid, ethanol, and phenols, which often generate off-flavours, were negatively correlated with mesophilic bacteria and LAB. It is interesting to note that salt content did not affect the performances of starter cultures and slightly influenced the metabolome of table olives. Sensory data demonstrated significant differences among samples registering the highest overall acceptability in the experimental sample at 5% of NaCl. The persistence of the L. paracasei N24 strain in experimental samples, at the end of the process, revealed its promising perspectives as starter cultures for the production of functional table olives with reduced salt content.